Input Subsidies -- The South Asian Experience by Simeon Ehui - Ehui, Simeon K. (2013)
IFPRI Policy Seminar "Input Subsidy Programs in Developing Countries What Works, What Doesn’t, and Why?" presentation by Simeon Ehui, The World Bank. Presented on 18 April 2013.